Analisis Praktik Pelaporan Berkelanjutan (Sustainability Reporting) pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Rofelawaty, Budi (Universitas Brawijaya, Indonesia, 2014)
Seeing the importance of the application of the company's sustainability reporting, this study aims to analyze the implementation of sustainability development are reflected in the operating sustainability and reporting on industrial companies listed on the Indonesian Stock Exchange. In this study, researcher conducted an analysis of the annual reports of 92 industrial companies listed in Indonesian Stock Exchange for the period ending in 2010. The results of this study that most of the industrial companies listed on the Stock Exchange are not fully adopted the Sustainability Report. It is seen that there are some items in Sustainability Reporting Guidelines need to be disclosed or communicated to stakeholders in a company's annual report still has not been disclosed (Such as, the company's concern for environmental issues, environmental policy or management of the company, company policies related to community social issues, and human rights for the company's policy on employees and the community around the company). Most of the industrial companies disclosing only about economic performance, about environmental and social performance still in the form of qualitative information or narrative form, not followed by calculation or quantitative information.